IFITM protein regulation and functions: Far beyond the fight against viruses - Friedlová, Nela; Zavadil Kokáš, Filip; Hupp, Ted R.; Vojtěšek, Bořivoj; Nekulová, Marta (Frontiers in Immunology, 2022)
Interferons (IFNs) are important cytokines that regulate immune responses through the activation of hundreds of genes, including interferon-induced transmembrane proteins (IFITMs). This evolutionarily conserved protein family includes five functionally active homologs in humans. Despite high sequence homology, IFITMs vary in expression, subcellular localization and function. The initially described adhesive and antiproliferative functions of IFITM proteins were drowned by the discovery of their antiviral properties. The large list of viruses inhibited by these proteins is constantly expanding, as are the possible mechanisms of action. In addition to their beneficial antiviral effect, IFITM proteins are often upregulated in a broad spectrum of cancers. IFITM proteins have been linked with most hallmarks of cancer, including tumor cell proliferation, therapeutic resistance, angiogenesis, invasion and metastasis. Recent studies have described the involvement of IFITM proteins in antitumor immunity. This review summarizes various levels of IFITM protein regulation and the physiological and pathological functions of these proteins, with an emphasis on tumorigenesis and antitumor immunity.